Design, synthesis and bio-evaluation of piperidines and CGRP peptides; Synthesis of substituted 6-(dimethylamino)-2-phenylisoindolin-1-ones for the inhibition of luciferase. - Anhettigama Gamaralalage, Medha Jaimini Gunaratna (Kansas State University, 2017)
Three research projects are described in this dissertation, and they are: (i) discovery of piperidine derivatives as T-type calcium channel inhibitors for the treatment of epilepsy and neuropathic pain and as protein disulfide isomerase inhibitors for the treatment of influenza viral infection; (ii) discovery of peptide-based calcitonin gene-related peptide receptor antagonists for the treatment of inflammatory pain; and (iii) synthesis of substituted 6-(dimethylamino)-2-phenylisoindolin-1-ones for the inhibition of luciferase. T-type calcium channels are important regulators of nervous system, and upregulated T-type calcium channel activities have been found to link to various types of neurological disorders, such as epilepsy and neuropathic pain. To discover novel T-type calcium channel blockers, a series of 1,4-disubstituted piperidine derivatives were designed and synthesized. Among them, compound 1-4 was found to be a good T-type calcium channel inhibitor with an IC₅₀ of 1 nM for Ca[subscript v]3.2 inhibition. It also showed 86% suppression of seizure induced death in mice and good in vivo analgesic effects on both thermal and mechanical pain thresholds in Spared Nerve Injury rat models. Therefore 1-4 can potentially be used as a T-type calcium channel blocker in the treatment of epilepsy and neuropathic pain. Influenza is a respiratory viral infection. Since viruses rely on host cell proteins for their entry, survival and replication, development of drugs targeting host cell proteins has identified as an effective strategy in controlling viral infections. We synthesized a series of 1,4-disubstituted piperidine derivatives for the inhibition of protein disulfide isomerase enzyme and influenza. Among them, 1-29 was found to possess strong anti-influenza activity (EC₅₀ = 2.5 µM). This suggests the potential use of piperidine scaffold in designing anti-influenza drugs in future. Calcitonin gene-related peptide (CGRP) receptor antagonism has been identified as a successful approach for the treatment of inflammatory pain. Therefore, a novel class of peptide antagonists of CGRP receptor was synthesized and screened for their binding affinities to the CGRP receptor and their analgesic effects on inflammatory-induced pain in rats. Among them, peptide 2-3 showed a higher binding affinity towards the CGRP receptor than previously reported peptide antagonists and exhibited analgesic effects up to 2 h in both Aδ and c-fiber pain tests. Therefore 2-3 indicates its potential use as a CGRP receptor antagonist in the treatment of inflammatory pain. Firefly luciferase is commonly used as a reporter in cells expressing a luciferase gene or its enzymatic activity under the control of a promoter of interest to assess its transcriptional activity. It has been found that some molecules such as molecules with carboxylic acid moiety can directly inhibit luciferase activity in cells. However, it is suggested that carboxylic acid moiety of the compounds may also be associated with side reactions in cells. Therefore, to study whether carboxylic acid moiety causes side effects, we designed two probe molecules, 3-1 and 3-2. Synthesis of probe molecule 3-2 is discussed. Synthesis of probe molecule 3-1 and further investigation of its luciferase inhibition will therefore be useful to understand the toxicity of carboxylic acid containing drugs in future.
Keywords: T-type calcium channel inhibitors; Protein disulfide isomerase inhibitors; Peptide-based calcitonin gene–related peptide receptor antagonists; Substituted 6-(dimethylamino)-2-phenylisoindolin-1-ones; Inhibition of luciferase; Piperidine derivatives